Unilateral chylothorax in a renal transplant recipient: A case report - Bil'awal Ramadhan Amuda; Gerhard Reinaldi Situmorang; Nur Rasyid (Urology Case Reports)
Chylothorax is accumulated lymphatic fluid in the pleural space. It rarely happens in end-stage renal illness patients, but possible causes are hospital-related. This case describes a 40-year-old man experiencing unilateral chylothorax after a kidney transplant. Left pleural cavity drainage shows a white, milky, cloudy, and odorless fluid. Fluid analysis findings were consistent with chylous. A chest tube was inserted, resulting in complete evacuation of fluid and total lungs expansion. No fluid accumulation was observed upon tube removal. Chylothorax is a rare complication of renal transplant. Conservative strategies with thoracostomy drainage and avoidance of oral intake and fluids are recommended.